FA'ĀLIYYATU NAMŪDZHAJ STAD FĪ TA'LĪMI AL-LUGHATI AL 'ARABIYYATI - Situmorang, Winda Syari; Nasution, Sahkholid (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This study was conducted because the observations at Az-Zakiyah Islamic School showed that many students were less active and motivated in Arabic classes, caused by factors such as lack of interest, and ineffective learning methods. This study aims to assess the effectiveness of the STAD (Student Team Achievement Division) learning model in learning the Arabic language in class VIII students of Az-Zakiyah Islamic School. This study used a pseudo-experimental approach with a one-group pretest-posttest design. In this design, the researcher measured the dependent variable (student learning outcomes) twice: once before the application of the STAD model (pre-test) and once after the application of the STAD model (post-test) to see changes in student learning outcomes in response to the intervention that the researcher conducted. The instruments included learning achievement tests (pre-test and post-test) and classroom observation sheets. The pre-test was used to obtain a baseline of students' level of understanding before the intervention. In contrast, the post-test was used to evaluate the impact of the intervention on students' learning outcomes after the implementation of the STAD learning model. The results showed a significant increase in student learning outcomes after the implementation of the STAD learning model. The mean score of students' pre-test was 61, while the post-test score increased to 73, indicating a 19% increase in effectiveness. Statistical analysis with a t-test for paired samples showed that the difference in pre-test and post-test scores was significant (t(19) = -10.162, p < 0.05). Classroom observations and interviews showed that the STAD model increased students' participation and cooperation in the learning process. Based on these findings, it can be concluded that the STAD learning model is effective in improving students' Arabic language learning outcomes in class VIII of Az-Zakiyah Islamic School.